Mapping Future Time Perspective Research among Indonesian Youth: A Scoping Review of Socio-Cultural Adaptation in the Age of Global Transformation - Dwi Nur Rachmah; Wiwin Hendriani; Primatia Yogi Wulandari (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
In the accelerating era of globalization and digital transformation, understanding how Indonesian youth perceive the future is crucial in psychology and education. Despite global advances in future time perspective (FTP) research, its socio-cultural dimensions in Indonesia remain underexplored. Using a scoping review guided by PRISMA criteria, this study systematically maps the scope, trends, and conceptual gaps in FTP research among Indonesian adolescents. Of the 178 identified studies, 17 met the inclusion criteria and were thematically synthesized into four themes: the evolution and contextual adaptation of FTP research in Indonesia, variables in FTP studies, conceptual and methodological contributions, and implications for youth counseling and development. The findings bridge Western and Indonesian FTP frameworks and emphasize the need for diverse qualitative, mixed, and longitudinal approaches. Future research should further explore socio-emotional and cultural dynamics while developing contextually grounded FTP-based interventions for Indonesian youth. Keywords: future time perspective, youth development, scoping review, socio-cultural adaptation, global transformation